Reliability evaluation of two interconnected power systems incorporating intermittency and seasonal variation in generation and load forecast uncertainty - Dulce, Elvin D.; Del Mundo, Rowaldo R. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
This study developed analytical and probabilistic models and methodology that simultaneously take into account the intermittency of wind power, the seasonal variation in hydro power, and the load forecast uncertainty in evaluating the reliability of two interconnected power systems. The intermittency of wind power is incorporated by using a sliding window approach with 7-hour period while the seasonal variation in hydro power is incorporated by considering the hourly generation. A seven-step approximation of the normal distribution is used for the load forecast uncertainty considerations. As applied to the Luzon-Visayas interconnected power system in the Philippines, the expected loss-of-load of the Luzon Grid in 2014 when assisted by the Visayas Grid is 52 hours/year. However, when the intermittency of wind power, the seasonal variation in hydro power, and the uncertainty of load forecast were considered, the loss-of-load expectation in the Luzon Grid increased to 95 hours/year. On the other hand, when the Luzon Grid is the assisting power system, the loss-of-load expectation in the Visayas Grid increased from the 12 hours/year to 33 hours/year. Therefore, there is a significant improvement in the calculated LOLE in two interconnected power systems when the intermittency and seasonal variation in generation and the load forecast uncertainty are simultaneously considered.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Interconnected electric utility systems -- Reliability. -- Philippines; Electric power systems -- Reliability